Reconfigurable buffer mechanism in switch fabric design - Hui-qun HUANG; Qin-rang LIU; You-jun BU; Feng-yu ZHANG (Tongxin xuebao)
Current research focused on the theoretic buffer size of routers.The reconfigurable buffer tried to improve the buffer utilization rate to optimize the system performance based on the on-demand design of the reconfigurable system.In fact,for current switching fabrics with fixed buffers,cell loss under burst traffics still could not be resolved at some ports despite abundant buffers were free.The reconfiguration mechanism was introduced into buffers,which broke the private occupancy of buffers by single ports and reconfigured buffers due to the real-time requirements of per port.Analysis and simulation results show that the reconfiguration mechanism could resolve the problem of resource consumption effectively,and improve the ultilization of buffers as well as save buffers with the same anti-burst performance.